Synthesis and characterization of dialdehyde cellulose nanofibers from O. sativa husks - Madivoli, Edwin S.; Kareru, Patrick G.; Gachanja, Anthony N.; Mugo, Samuel; Makhanu, David Sujee (My University, 2019)
Periodate oxidation of cellulose breaks the C2–C3 bond of the glucose repeating units forming two vicinal aldehyde groups that are amenable to further reactions. In this article, effects of reaction conditions during the oxidation such as reaction time, oxidant concentration, and temperature on the aldehyde content were investigated and an optimized reaction condition identified. The synthesis of 2,3-dialdehyde cellulose (DAC) was confirmed by scanning electron microscopy, transmission electron microscopy (TEM), Fourier-transform infra-red spectroscopy (FT-IR), differential scanning calorimetry, thermal gravimetric analysis and wide-angle X-ray diffractometer (WXRD). Formation of dialdehyde cellulose (DAC) was confirmed by the appearance of carbonyl peak in FT-IR spectra while a decrease in crystallinity of the fibers as a result of oxidation was confirmed by WXRD. Morphological changes during oxidation were observed using SEM while the size of the fibers was confirmed by TEM, which showed the average length of the fibers decreased after oxidation as compared to native cellulose. Thermal degradation studies revealed that oxidation of cellulose decreased the thermal stability of the polymer as compared to native cellulose and was dependent on the aldehyde content. In conclusion, oxidation of native cellulose to dialdehyde cellulose had a profound effect on the thermal stability, degree of crystallinity, size and morphology of the polymer.
Keywords: CNF; dialdehyde cellulose; SEM; TEM; DAC